Heavy metals containment by vertical cutoff walls backfilled with novel reactive magnesium-activated slag-bentonite-sand: Membrane and diffusion behavior. (15th December 2021) - Fu, Xian-Lei; Wu, Hao-Liang; Zhang, Run; Jiang, Zhe-Yuan; Reddy, Krishna R.; Du, Yan-Jun
Abstract: This study aims to investigate the membrane and diffusion behavior of a novel vertical cutoff wall backfill comprised of reactive magnesium-activated slag, bentonite and sand (referred as MSBS backfill) for the containment of heavy metals in groundwater. The MSBS backfill specimens were subjected to a series of multi-stage chemico-osmotic tests using Pb(NO3 )2 and Zn(NO3 )2 solutions at different concentrations. Chemico-osmotic efficiency coefficient, effective diffusion coefficient, and retardation factor of the backfills were computed. For computing chemico-osmotic efficiency coefficient, the theoretical chemico-osmotic pressure differences were computed using both van't Hoff equation and water activity method. The results showed that the MSBS backfill exhibited semipermeable membrane behavior in tested solutions. The chemico-osmotic efficiency coefficients of the backfills decreased, whereas effective diffusion coefficients of heavy metal cations remained nearly constant, and retardation factors of heavy metal cations increased slightly with the increase of metal concentration. For the range of concentrations of Zn(NO3 )2 in this study, the maximum percent error of theoretical chemico-osmotic pressure difference calculated using van't Hoff equation relative to that calculated using water activity method was 14.4%. A comparative assessment of reported chemico-osmotic efficiency coefficient, effective diffusion coefficient, and retardation factor values for various soil-bentonite backfills and geosynthetic clay liners with those for MSBS backfill was performed. Overall, the results are useful to assess containment performance of MSBS vertical cutoff walls at metal-contaminated groundwater sites. Graphical abstract: Image 1 Highlights: New reactive magnesium-activated slag, bentonite and sand (MSBS) backfill is proposed. Van't Hoff equation yields significant error in calculating chemico-osmotic efficiency coefficient in Zn(NO3 )2 solution. Effective diffusion coefficients remain constant with increasing concentration. Comparative assessment of membrane and diffusion behavior for engineered barriers is performed.